2002
DOI: 10.1038/labinvest.3780425
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Is Exposed to the Extracellular Matrix at Invasive Sites in Basal Cell Carcinomas

Abstract: SUMMARY:We have previously shown, by light microscopy, that the level of expression of CD44 (pan-CD44, CD44v3, CD44v5, and CD44v6) in human basal cell carcinomas is related to growth pattern and invasiveness (Br J Dermatol 1099;140:17-25). We have now studied the fine distribution of these CD44 isoforms in the same tumors using immunoelectron microscopy. Despite the strong differences in the level of expression in tumor areas with different growth patterns, CD44 was consistently found almost exclusively at int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Similar implications can be made about our observed downregulation of the hyaluronic acid receptor CD44. Previous studies have demonstrated that CD44 is only upregulated at invasive sites in BCCs [50], or in rare forms of metastatic BCC [51]. Ordinarily however, BCC exhibits low levels of CD44.…”
Section: Discussionmentioning
confidence: 99%
“…Similar implications can be made about our observed downregulation of the hyaluronic acid receptor CD44. Previous studies have demonstrated that CD44 is only upregulated at invasive sites in BCCs [50], or in rare forms of metastatic BCC [51]. Ordinarily however, BCC exhibits low levels of CD44.…”
Section: Discussionmentioning
confidence: 99%
“…The CD44 family has a binding capacity for ECM components, particularly hyaluronan (41). The interaction between CD44 and hyaluronan is known to be involved in tumor invasion in some malignant neoplasms (42, 43). We believe that ECM plays a role in niche construction for CSCs in AdCC.…”
Section: Discussionmentioning
confidence: 99%
“…First, expression of CD44 by the tumour cells can increase the interaction with endothelial cells and transmigration across an endothelial monolayer (Fujisaki et al, 1999;Mine et al, 2003;Draffin et al, 2004;Ratliff, 2005). Second, in a wide variety of systems, increased CD44 expression has been shown to correlate strongly with increased invasive potential of tumour cells Jothy, 1999, 2001;Dingemans et al, 2002;Kobayashi et al, 2002;Bourguignon et al, 2003;Xu and Yu, 2003;Kim et al, 2004;Miletti-Gonzalez et al, 2005) and in particular, increasing evidence points to an important role for CD44 in mediating directional cell migration (Alstergren et al, 2004;Avigdor et al, 2004;Zhu et al, 2004Zhu et al, , 2005Miletti-Gonzalez et al, 2005;Tzircotis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%